2005
DOI: 10.1007/s00404-005-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

The relation of increased uterine artery blood flow resistance and impaired trophoblast invasion in pre-eclamptic pregnancies

Abstract: Doppler ultrasonography is not only a non-invasive method for evaluating fetal status in pre-eclamptic pregnancies, but it also correlates with partial trophoblastic invasion in spiral arteries, which contributes to the pathophysiologic mechanisms involved in pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 14 publications
2
35
0
1
Order By: Relevance
“…High resistance uterine artery indices were previously found to correlate with decreased endovascular trophoblast invasion of decidual spiral arteries [48]. This finding is consistent with the correlation between high uterine artery resistance index and decreased endovascular trophoblast invasion of decidual and myometrial spiral arteries in women with preeclampsia [49]. In the first trimester decidual tissues from pregnancies with high uterine artery index, Cartwright et al identified perturbed gene expression and aberrant dNK cell phenotype, as well as impaired regulation of trophoblast function by dNK cells in vitro [35].…”
Section: Decidual Gene Expression and Function Before Onset Of Clinicsupporting
confidence: 84%
“…High resistance uterine artery indices were previously found to correlate with decreased endovascular trophoblast invasion of decidual spiral arteries [48]. This finding is consistent with the correlation between high uterine artery resistance index and decreased endovascular trophoblast invasion of decidual and myometrial spiral arteries in women with preeclampsia [49]. In the first trimester decidual tissues from pregnancies with high uterine artery index, Cartwright et al identified perturbed gene expression and aberrant dNK cell phenotype, as well as impaired regulation of trophoblast function by dNK cells in vitro [35].…”
Section: Decidual Gene Expression and Function Before Onset Of Clinicsupporting
confidence: 84%
“…[100] In another study, myometrial spiral artery invasion was absent in 6 of 12 mild preeclamptics with a mean gestational age of 37 weeks and in 15 of 20 severe preeclamptics with a mean gestational age of 34 weeks. [101] Similarly, spiral artery vascular remodeling was abnormal not only in all 21 cases of preeclampsia with FGR but also in 8 of 9 cases of preeclampsia without FGR. [102] In a study of myometrial spiral artery remodeling, it was absent in 1 of 26 normal pregnancies, 7 of 11 preeclamptics with FGR, and 6 of 22 preeclamptics without FGR.…”
Section: Subsets Of Preeclampsiamentioning
confidence: 99%
“…This segment retains a hypertrophic muscular structure, although interstitial trophoblasts are present, sometimes in excessive numbers (3). The defective transformation is more severe in the myometrial, than in the decidual, segments (8, 29). …”
Section: Introductionmentioning
confidence: 99%